Napza Dalam Perspektif Hukum Islam - Syarifuddin Syarifuddin (Iqtishaduna: Jurnal Ilmiah Ekonomi Kita)
Drug abuse is a social problem that has a dimension which is very extensive and complex that is difficult to overcome completely and thoroughly. This is due, because, so far, have not found an effective method of prevention, both in preventing,  preventive, repressive, and rehabilitative. Drug abuse, in addition, to be very bad for the user himself, will also be born destructive actions that could harm and threaten social systems and institutions that had been built. In implicit, the drug was not mentioned in the Koran and Hadith. However, by understanding the substance of the Quranic text and referring it to the various Hadith of the Prophet., so, the drug can be the wine, especially if judging from the indications of the law (illat al-hukm) of intoxicating. Thus, the law that is applicable to the wine also applies to a drug. Analyzing various indications and the drug contained excess, then the analogue qualifications are superlative degree, or in the terminology of usual called qiyas awlawi. For inherent characteristics with far more dangerous drug contained Instead of alcohol (The wine). As a logical consequence, in view of the speakers, sanctions imposed actually is more severe than the sanction given to those who just simply be a drinker. In this case, the speakers are more likely to regard punishment as an alternative tazir (choice of law/sanctions) that are most relevant. The more severe the punishment is given (by judges) is better (the upholder the better).